Implementasi Khiyar ‘Aib Pada Transkasi Jual Beli Produk Fashion Muslim di Butik Inayah Menurut Hukum Islam - Safera, Nurul (STAI Al-Musaddadiyah Garut, 2025)
Khiyar 'aib is the buyer's right to cancel a transaction if a defect is found in the purchased product. This study investigates the practice of khiyar 'aib in the sale and purchase of Muslim fashion products at Butik Inayah, located in Serang City. The study is motivated by findings that the seller does not take responsibility for defective products returned by consumers, arguing that the product's condition no longer meets store standards, despite the hangtag remaining attached. The objective of this research is to examine the implementation, legal conditions, and Islamic legal review of khiyar 'aib in transactions involving Muslim fashion products at Butik Inayah. A qualitative approach was employed using a case study method. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman model, which involves data reduction, data display, and conclusion drawing. The results show that the implementation of khiyar 'aib at Butik Inayah does not fully align with the principles of Islamic law. The seller does not offer a refund or replacement for defective goods, based on reasons that do not meet the valid conditions of khiyar 'aib. From the perspective of Islamic law, such practices do not reflect proper consumer protection as mandated by the sharia. Keywords: Implementation, Khiyar ‘Aib, Sales Transactions, Butik Inayah, Islamic Law.